Investigation of Delays in Construction Projects: The Case of Jordan-Amman - Yassin, Abdallah Ahmad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Delays in the construction could be defined as a delay in project delivery according to the plan presented during the specified time. The issue of development delays is a worldwide marvel, numerous specialists have led a few investigations to discover the fundamental factors and reasons of postpone causes. It is a standard in the development business that accomplishment of the conveyed venture is estimated by; the timetable season of the specific undertakings inside the cost issues and as per the pre-depicted guidelines of required quality. Consequently, it is imperative to recognize and arrange the potential factors that cause delays during the conveyance of the undertaking. As of recently, numerous investigations are closed and a lot more are as yet under advancement to distinguish the variables causing delay in development extends nonetheless, in handy terms, Jordanian development industry experts despite everything experiences absence of mindfulness on the reasons for venture delays henceforth, no successful insurances are thought of. The postponements in development must be decreased if their sources are known. Thusly, this investigation intends to explain the variables that can bring about development time-expansion and discover arrangements of augmentation time issues in the business of development in Jordan. Inside this unique circumstance, thinking about the social and social habits of the business experts, a framework is proposed with the intention of breaking the squares of traditionally adopted project management principles of Jordanian construction industry professionals. In this research, with the help of conducted questionnaire targeting competent authorities and other stakeholders, project delay factors are identified and grouped based on their roots. This study revealed that, the most critical factors that lead can be resulted in delays in Jordan such as; Delay for interim budget of the owner/client to contractors and the difficulties of providing funds into projects by the contractors. Client-related delays, in this study was determined as a serious problem that can result in delay such as; designing issue, and labors related delays. In addition, the period of the project and cost overruns are the typical consequences in time extension. In Jordanian construction companies ignore the causes of delays until they actually occur and unavoidably, when this happens, it becomes too costly to reschedule as wasted time can never be recovered. For this reason, a framework will be created, along with proposing appropriate solutions to these delays to contribute to quick decision-making before or after the occurrence of these delays.

ÖZ: İnşaat yapımındaki gecikmeler, belirtilen süre boyunca sunulan plana göre proje teslimatındaki gecikme olarak tanımlanabilir. İnşaat gecikmeleri sorunu küresel bir fenomendir ve birçok inşaat yönetimi uzmanı inşaat gecikmelerinin nedenlerini ve etkilerini araştırmaya çalışmıştır. İnşaat sektöründe teslim edilen projenin başarısını; Projelerin bütçe dahilinde ve önceden tanımlanmış kalite standartlarına uygun olarak zamanında teslim edilmesi belirler. Bu nedenle projenin teslimi sırasında gecikmelere neden olan potansiyel faktörlerin belirlenmesi ve sınıflandırılması çok önemlidir. Şimdiye kadar, inşaat projelerinde gecikmeye neden olan faktörleri belirlemek için pek çok çalışma yürütülmüş ve daha pek çoğu henüz devam etmektedir, ancak pratik olarak Ürdünlü inşaat sektörü uzmanları, proje gecikmelerinin nedenleri konusunda hala bilinçsizlikten mustariptir. İnşaattaki gecikmeler, ancak kaynakları biliniyorsa azaltılabilir. Bu nedenle, bu çalışmanın temel amacı, Ürdün'deki inşaat sektöründe yaşanan gecikmelerin başlıca nedenlerini ve bu gecikmelerin çözümlerini belirlemektir. Bu bağlamda, sektör profesyonellerinin sosyal ve kültürel tavırları dikkate alınarak, Ürdünlü inşaat sektörü öncülerinin geleneksel olarak benimsediği kalıplaşmış proje yönetimi ilkelerini çürütmek amacıyla bir çerçeve önerilmektedir. Bu araştırmada, yetkili makamlara ve diğer paydaşlara yönelik yürütülen anket yardımı ile proje gecikme faktörleri tanımlanmakta ve köklerine göre gruplandırılmaktadır. Bu çalışma, Ürdün'deki proje gecikmelerine yol açan en önemli faktörlerin mal sahibi / işveren tarafından tamamlanan işin yüklenicilere ödenmesindeki gecikmeler ve müteahhitlerin projelere fon sağlamadaki zorluklar gibi finansal sorunlar olduğunu ortaya koymuştur. Müşteriyle yaşanan gecikmeler, gecikmelere neden olan en önemli gruplar olarak sıralanır, ardından tasarımcı ile ilgili gecikmeler ve işçilikle ilgili gecikmeler gelir. Dahası, zaman ve maliyet aşımları, inşaat projelerindeki gecikmelerin tipik sonuçlarıdır ve ne yazık ki, çoğu Ürdünlü şirket gecikmelerin nedenlerini gerçekten meydana gelinceye kadar görmezden gelir ve bu olduğunda kaçınılmaz olarak, boşa harcanan zaman asla geri kazanılamayacağından yeniden planlamak sanıldığından çok maliyetli hale alır. Bu nedenle, Ürdün inşaat sektöründeki gecikmelerin en önemli nedenlerini belirlemek için bir çerçeve oluşturulacak ve bu gecikmelerin meydana gelmesinden önce veya sonra hızlı karar alınmasına katkı sağlayacak çözüm önerilerinde bulunulacaktır.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2020. Supervisor: Assoc. Prof. Dr. Tolga Çelik
Keywords: Civil Engineering Department; Construction Projects--Delays; Construction industry--Management--Production scheduling--Construction projects; Construction Delay, Project Delivery, Delay Factors, Jordanian Construction Industry